Observation of Stripe Superstructure in the β-Two-Phase Coexistence Region of Cholesterol–Phospholipid Mixtures in Supported Membranes - Tabaei, Seyed R. (2016)
Visualization of phase coexistence in the β region of cholesterol–phospholipid mixtures consisting of high cholesterol concentrations has proved elusive in lipid bilayers. Here, using the solvent-assisted lipid bilayer approach to prepare supported membranes with high cholesterol fractions close to the cholesterol solubility limit, we report the observation of coexisting liquid phases using fluorescence microscopy. At ∼63 mol % cholesterol, supported membranes consisting of mixtures of DOPC and cholesterol exhibit large-area striping reminiscent of the stripe superstructures that characterize the proximity of the second critical point in the miscibility phase diagram. The properties of the two phases are consistent with condensed complex-rich and cholesterol-rich liquids. Both phases exhibit long-range lateral mobility, and diffusion through a given phase is favored over hopping across the phase boundary, producing an “archipelago effect” and a complex percolation path.